A random walk down Wuhan street event analysis of the impact of COVID-19 on the stock returns of vaccine firms publicly listed in the US - Berdin, Dylan Benjamine Alyssandra S.; Laureta, Alfonso Gabriel A.; Mendoza, Adrian R. (Quezon City School of Economics, University of the Philippines Diliman, 2022)
Those who can spot a crisis coming are bound to prepare for it, while those who could promise to end it are bound to profit. The unprecedented COVID-19 pandemic saw unprecedented movements in stock prices. From when mysterious pneumonia cases of unknown cause were first reported in Wuhan on December 31, 2019, to when the Pfizer-BioNTech COVID-19 vaccine was given full FDA approval, COVID-19 vaccine firms like Moderna, Novavax, and BioNTech have gained 5428.63%, 3065.95%, and 2583.29% respectively. Our study sought to investigate changes in stock prices preceding principal events related to the emergence and progression of COVID-19, as well as the vaccination efforts against it. We calculate for cumulative abnormal returns by using the Event Study Methodology (ESM) to quantify how stock returns of COVID-19 vaccine firms are impacted by (1) the first official public report of mysterious pneumonia cases in Wuhan, (2) the WHO’s declaration of COVID-19 as a pandemic, and (3) the issuance of emergency use authorization for COVID-19 vaccines. Results show cumulative abnormal returns
across specific COVID-19 vaccine firms on all event dates. We observe premature buying and premature selling activity prior to actual public announcements, and link this to asymmetric information, causing limits to market efficiency. However, as per the strong-form efficient market hypothesis, we maintain this as a reflection of insider information and regard it as an efficient market response.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references and appendix.
Keywords: Vaccines; Biotechnology; COVID-19 (Disease) -- Vaccination; COVID-19 (Disease).